EDUCATION ON THE CAUSE OF PARENT COMPLEX’ TRAGIC FATE - Chong Chilung (International Scientific and Current Research Conferences, 2021)
Parent complex the King is an extraordinary Greek misfortune by Sophocles. Aristotle at any point accepting it as the example to clarify his outlook in his renowned Poetics. The pursuers consistently are contacted profoundly by the hopeless destiny of Parent complex, yet who causes the event of the awful sins? Parent complex needs to escape from his horrendous destiny, be that as it may, very much like a manikin of God, understands God's arrangement.